2016
DOI: 10.1109/tmi.2016.2529665
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Preserving Color Normalization and Sparse Stain Separation for Histological Images

Abstract: Staining and scanning of tissue samples for microscopic examination is fraught with undesirable color variations arising from differences in raw materials and manufacturing techniques of stain vendors, staining protocols of labs, and color responses of digital scanners. When comparing tissue samples, color normalization and stain separation of the tissue images can be helpful for both pathologists and software. Techniques that are used for natural images fail to utilize structural properties of stained tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
413
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(422 citation statements)
references
References 27 publications
1
413
0
8
Order By: Relevance
“…However, the degree of prognostic enhancement did associate with the tonal range width as the best‐performing gamma correction by the exponent of 0.1 produced the narrowest, whereas the weakest‐performing contrast‐related normalisation algorithms produced the widest tonal range modification. This result was very surprising because colour variation between histopathology images has long been a recognised problem in image analysis (Li & Plataniotis, ), with image normalisation by stretching of pixel intensity range as the main strategy for the image enhancement in various applications (Li & Plataniotis, ; Bejnordi et al ., ; Vahadane et al ., ). Taken together, based on our data we confirm the known prognostic benefit of image tonal histogram normalisation and contribute the novel finding that nonnormalising tonal compression performs even better.…”
Section: Discussionmentioning
confidence: 97%
“…However, the degree of prognostic enhancement did associate with the tonal range width as the best‐performing gamma correction by the exponent of 0.1 produced the narrowest, whereas the weakest‐performing contrast‐related normalisation algorithms produced the widest tonal range modification. This result was very surprising because colour variation between histopathology images has long been a recognised problem in image analysis (Li & Plataniotis, ), with image normalisation by stretching of pixel intensity range as the main strategy for the image enhancement in various applications (Li & Plataniotis, ; Bejnordi et al ., ; Vahadane et al ., ). Taken together, based on our data we confirm the known prognostic benefit of image tonal histogram normalisation and contribute the novel finding that nonnormalising tonal compression performs even better.…”
Section: Discussionmentioning
confidence: 97%
“…Sethi, et al [17] used standard deviation to describe intra-image variability and demonstrated that the Khan, et al [16] and Vahadane et al [11] algorithms exhibited variability similar in magnitude to the original image’s variability, concluding that much of the information in the original images was not lost. We noted a similar property in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has used color normalization as a tool to transform H&E images to conform to a standardized color target in a manner that minimizes the loss of useful information in the image. Many of these approaches have used intensity thresholding [8, 9], histogram normalization [10], stain separation [1113], and color deconvolution [14–16] to characterize or normalize H&E images, with varied levels of success. These algorithms shared a common strategy in that normalization can be approached from the standpoint of color analysis: that the superposition of stains that form the color basis of an image can be deconstructed into its constituents and recombined to conform to a target.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we asked an expert to select a bag of dominantly stained hematoxylin and eosin pixels. In the future, this process can be automated by calculating stain vectors for hematolyxin and eosin over a population of H&E slides and using these vectors to derive representative pixels [15], [16]. …”
Section: Methodsologymentioning
confidence: 99%